Multiple primary malignancies for squamous cell carcinoma and adenocarcinoma of the esophagus - Chen, Dongni; Fan, Ningbo; Mo, Junxian; Wang, Weidong; Wang, Ruiqi; Chen, Youfang; Hu, Jia; Wen, Zhesheng (Journal of Thoracic Disease; Vol 11, No 8 (August 31, 2019): Journal of Thoracic Disease, 2019)
Background: Patients with esophageal cancer (EC) frequently have multiple primary cancers. We conducted the present study to assess the risk of multiple primary malignancies for patients with squamous cell carcinoma (SCC) and adenocarcinoma (AC) of the esophagus and to investigate the influence of multiple primary tumors on the prognosis of EC patients. Methods: Using the data of 44,091 EC patients from the Surveillance Epidemiology and End Results (SEER) database, we calculated the standardized incidence ratios (SIRs) for overall multiple primary cancers and cancers at particular sites among EC survivors. The SIRs of esophageal SCC and AC patients were compared using Poisson regression. The Kaplan-Meier (KM) method was used for survival analysis. Results: Multiple primary cancer risk was significantly increased among both esophageal SCC and AC survivors (SIR: 2.28 and 1.57, respectively; P